Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/adma.201604603
|View full text |Cite
|
Sign up to set email alerts
|

Panchromatic Sequentially Cast Ternary Polymer Solar Cells

Abstract: A sequential-casting ternary method is developed to create stratified bulk heterojunction (BHJ) solar cells, in which the two BHJ layers are spin cast sequentially without the need of adopting a middle electrode and orthogonal solvents. This method is found to be particularly useful for polymers that form a mechanically alloyed morphology due to the high degree of miscibility in the blend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 69 publications
(122 reference statements)
1
98
0
Order By: Relevance
“…By using SMAs with similar surface tensions prior to ternary device fabrication, we were able to predict whether the molecular acceptors have the potential to form reasonably small domains. [79] However, if the mechanical alloy leads to the formation of new electronic states, the Coherence lengths are calculated using Scherrer equation based on the full width at half-maximum of each peak; b) Obtained by fitting the peaks at Q values around 0.47, which is assigned to the ITIC-Th (100) scattering. [16,63,73,78] Such close contact could potentially lead to the formation of a mechanical alloy, which alone may not be beneficial for device performance.…”
Section: The Role Of Surface Tension and Interfacial Tensionmentioning
confidence: 99%
“…By using SMAs with similar surface tensions prior to ternary device fabrication, we were able to predict whether the molecular acceptors have the potential to form reasonably small domains. [79] However, if the mechanical alloy leads to the formation of new electronic states, the Coherence lengths are calculated using Scherrer equation based on the full width at half-maximum of each peak; b) Obtained by fitting the peaks at Q values around 0.47, which is assigned to the ITIC-Th (100) scattering. [16,63,73,78] Such close contact could potentially lead to the formation of a mechanical alloy, which alone may not be beneficial for device performance.…”
Section: The Role Of Surface Tension and Interfacial Tensionmentioning
confidence: 99%
“…Recently, scientists proposed a novel method to continuously spin‐coat two kinds of blending solutions of FTAZ:PC 71 BM and PDPP3T:PC 71 BM. At the same time, it is also reported that an additional acceptor layer (IDIC) was inserted between the binary system active layer (PTB7‐Th:PC 71 BM) and ZnO electron transport layer to increase the device efficiency 30,31. However, such a method is unable to separate the donors and the acceptors, the vertical phase separation of the active layers are still not well regulated.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is also reported that an additional acceptor layer (IDIC) was inserted between the binary system active layer (PTB7-Th:PC 71 BM) and ZnO electron transport layer to increase the device efficiency. [30,31] However, such a method is unable to separate the donors and the acceptors, the vertical phase separation of the active layers are still not well regulated. There are also related literature reporting the use of orthogonal solvents or simultaneously…”
mentioning
confidence: 99%
“…[1][2][3] It has been recognized as a great promising substitute for siliconbased photovoltaic with advantages of light weight, inexpensive cost, and largearea flexible preparation with roll-to-roll (R2R) process. [14,[21][22][23][24][25][26][27] As an efficient and new type of device structure, ternary OSCs generally consist of multidonor and one acceptor or one donor and multiacceptor. [14,[21][22][23][24][25][26][27] As an efficient and new type of device structure, ternary OSCs generally consist of multidonor and one acceptor or one donor and multiacceptor.…”
Section: Introductionmentioning
confidence: 99%
“…Although the authors mentioned the good miscibility between PTB7-Th and BTR, the impact of miscibility on the corresponding performance of the solar cells was not discussed. [22] Unfortunately, the PCE value of ternary system is much lower than the binary system. [36,45] Although the miscibility is recognized to be an important factor in determining the performance of cells, no detailed quantitative description of miscibility is presented.…”
Section: Introductionmentioning
confidence: 99%